Pyknodysostosis with Hearing Impairment - Ashraf, Mohd; Farooq, Arshad; Dar, Tanveer I; Wani, Khursheed A (Journal of Medicine, 2010)
Pyknodysostosis is a rare seclerosing bone disease that has autosomal recessive trait. It is characterized by small stature, diffuse osteosclerosis with tendency to transverse fractures, acro-osteolysis of fingers, with flattened and grooved nails. Other features include persistence of fontanelles, delayed closure of sutures, wormian bones, absence of frontal sinuses and obtuse mandibular gonial angle with relative mandibular prognathism. We report a 9-yearold girl having features of pyknodysostosis with progressive hearing impairment, in the form of otosclerosis. Keywords: Craniofacial abnormalities; Hearing impairment; Otosclerosis; Pyknodysostosis; Seclerosing bone diseases. DOI: 10.3329/jom.v11i2.5475 J MEDICINE 2010; 11 : 202-204